Combined effects of climate change and environmentally relevant mixtures of endocrine disrupting compounds on the fitness and gonads' maturation dynamics of Nucella lapillus (Gastropoda). (May 2023) - Morais, H.; Arenas, F.; Cruzeiro, C.; Galante-Oliveira, S.; Cardoso, P.G.
Abstract: Coastal areas are affected by multiple stressors like climate change and endocrine disruptors (EDCs). In the laboratory, we investigated the combined effects of increased temperature and EDCs (drospirenone and mercury) on the fitness and gonads' maturation dynamics of the marine gastropod Nucella lapillus for 21 days. Survival was negatively affected by all the stressors alone, while, in combination, a synergistic negative effect was observed. Both chemicals, as single factors, did not cause any effect on the maturation stage of ovaries and testis. However, in the presence of a higher temperature, it was clear a delay in the maturation stage of the ovaries, but not in the testis, suggesting a higher negative impact of the stressors in females than in males. In summary, drospirenone caused a low negative impact in aquatic species, like gastropods, but in combination with other EDCs and/or increased temperature can be a matter of concern. Graphical abstract: Unlabelled Image Highlights: Combined Temp, Hg and DRO caused a synergistic negative effect on survival rate. Higher Temp plus EDCs caused delay in ovaries maturation stage. Higher negative impact of stressors was in females than males.